Simultaneous determination of multiple persistent organic pollutants in soil by ultrasonic extract-gas chromatography-mass spectrometry - ZHANG Hao; HUANG Ronglang; CHEN Minyan; JIANG Jun; YANG Lan; CHEN Jian; LÜ Zhijiang; LIAO Min; WANG Haizhen; XU Jianming (浙江大学学报. 农业与生命科学版)
A method for simultaneous extraction, purification, and determination of persistent organic pollutants (POPs) in soil, such as polychlorinated biphenyls, polybrominated diphenyl ethers, and polycyclic aromatic hydrocarbons, was developed in this study. The optimum conditions for extraction and purification were as follows: Soil samples were extracted ultrasonically three times with acetone/n-hexane (1∶‍1, by volume), followed by purification with Florisil solid-phase extraction column, and eluted by 12 mL of n-hexane/dichloromethane (9∶1, by volume) mixture solution. The eluant was concentrated by gentle N2 streams and finally quantified by gas chromatography-mass spectrometry (GC-MS) with PCB209 as the internal standard. Except for 2, 2′, 3, 3′, 4, 4′, 5, 5′, 6, 6′-decabromodiphenyl ether (BDE209), the other 41 POPs were efficiently separated within 23.83 min. Excellent linearity was observed in the concentration range of 20-1 000 µg/L for all POPs with the coefficients of determination (R2) of 0.997 5-0.999 9. The detection limits of 42 POPs were 0.04-1.19 ng/g, and the spiked recoveries ranged from 71.04% to 120.89% with relative standard deviations of 0.88%-6.29%, and intra- and inter-day reproducibility variations were less than 11%. In conclusion, this method greatly reduces time and workload and is characterized by simple operation, good accuracy, and high sensitivity. It can be widely applied to the determination and analysis of POPs in soil, such as e-waste disposal site soil, which will facilitate further studies on the fate and risk assessment of POPs.